Accuracy, precision and reliability in anthropometric surveys for ergonomics purposes in adult working populations: A literature review - Viviani, C. (2018)
Anthropometric surveys are the most common method of gathering human morphometric data, used to design clothing, products and workspaces. The aim of this paper was to assess how current peer reviewed literature addresses the accuracy, reliability and precision regarding manual anthropometric surveys applied to adult working populations in the field of ergonomics. A literature review was performed in two electronic databases for finding relevant papers. A total of 312 papers were reviewed, of which 79 met the inclusion criteria. The results shown that the subjects of these publications are poorly addressed, so that only 27 studies mentioned at least one of the terms and none of the studies evaluated all of the terms. Only one paper mentioned and assessed precision and reliability of the measurement procedure. Furthermore, none of the publications evaluated accuracy. Moreover, the reviewed papers presented large differences in the factors that affect precision, reliability and accuracy. This was particularly clear in the measurer technique/training, measurement tools, subject posture and clothing. Researchers in this area should take more rigorous approaches and explicit indicators with their results should be presented in any report. Relevance for industry: It is important that scientific literature related to manual anthropometric measurements uses methods for assessing measurement error, since these data are often used to design clothing and workspaces as well as to calibrate non manual methods such as 3D scanners. (C) 2018 Elsevier B.V. All rights reserved.